Estudo da mistura comercial dolomita-quartzo, dopada com Hg(I), Cd(II) e Cr(III), para adsorção de H2S - Silva, Francisco das Chagas Beserra da (2013)
The present work was to carry out a study on the adsorption of hydrogen sulfide (H2S) in arrays synthesized from a commercial clay mineral formed by a mixture of dolomite and quartz. To produce the ion exchange matrix were made using aqueous solutions of salts of cobalt II chloride hexahydrate (CoCl2.6H2O) II cadmium nitrate tetrahydrate (Cd (NO3)2.4H2O) I mercuric chloride (HgCl) nitrate and chromium III pentahydrate (Cr (NO3)3.5H2O). The arrays were subjected to hydrogen sulphide gas passage for one hour. To check the amount of gas adsorbed was used gravimetric process. The best result was in the adsorption matrix doped with cadmium and the solution retained for a longer time than the largest amount of H2S was the cobalt matrix. The matrix unmodified exhibited poor adsorption capacity. The characterization of the matrices were used XRD, XRF and IV. Mother with cadmium showed a high capacity in ion exchange, because the percentage of cadmium increased from 0% to 81.38% by replacing atoms of calcium and silicon which increased from 96.54% to 17.56% and 15, 72% to 0.32%, respectively, but also the best performance in adsorption of H2S adsorbing 11.89507 mg per gram of matrix